Occupational Safety and Health Risk Analysis with HIRA in Locomotive Maintenance at PT KAI (Persero) Daop VI Yogyakarta Locomotive Depot - Widagdo, Suryo; Widodo Hariyono (Universitas Ahmad Dahlan, 2024)
Background: Occupational health and safety was an important aspect in the world of work to get degree of health productively, prosperous and free from work disease. Risk management is required which includes hazard identification, risk analysis, likelihood and consequence, risk level, and risk treatment with Hazard Identification and Risk Assessment (HIRA). The research location in the unit sarana dipo locomotive PT. Kereta Api Indonesia (Persero) Daerah Operasi VI Yogyakarta it aims to analyze occupational safety and health risks in process of locomotive maintenance. Method: This research used a qualitative descriptive by collect data in the form of words and images. It was due to the application of qualitative methods, in addition to all the things collected will be examined. The approach used to a case study approach by determining in the form of program, activities, or a group of related individuals and this study consists of 6 informants. Results: The results showed in Yogyakarta dipo locomotive unit such as gravity hazard, heat from diesel engine, limited space, noise, oil, heavy work equipment, heavy work media, electricity and dust. In the risk assessment stage there are 2 hazards with extreme risk category, 3 high risk, 9 moderate, 4 low risk categories. Conclusion: The risks from the job of locomotive maintenance were falling from the top of the locomotive, electroucted, pinched, falling tools, exposed to engine heat, exposure form noise, dust, wind pressure, and oil and oil slips. Administrative risk control in the form of Standart Operational Procedure (SOP) and provision of Personal Protectibe Equipment (PPE).